Effects of electrospinning parameters on carrageenan-based nanofibers fabrication: article - Rashid, Dayangku Elma Rashidah; Ishak, Abdul Aziz; Abu Bakar, Noor Fitrah (2019)
Polymer nanofibers are known to exhibits excellent properties that made it very useful in producing and development of tissue engineering, filtration, biochemical engineering and many more. Nowadays, electrospinning is the most commonly and preferably used to manufacture these polymer nanofibers because the nanofibers produced using this technique ably to produce a high surface area to volume ratio. Carrageenan-based nanofibers were prepared by electrospinning of polyvinyl alcohol (PVA)/carrageenan (CAR) solution. The solution is made of 1 w/v% of CAR solution and 13 w/v% fully hydrolyzed PVA solution. The solutions were mixed with a ratio of 70:30, creating the polymer solution, FH PVA/CAR solution. The morphology and diameters of the nanofibers were observed by using a scanning electron microscope (SEM), the contact angles on the nanomembrane were measured by static micro-drop observation, and the effects of electrospinning parameters including voltage, distance between tip of needle and collector, as well as the flow rate of the solution were observed.